Short and Medium-chain Fatty Acid Profile of Goat Milk Fed with Pineapple Peel Silage - Raguati, Raguati; Afzalani, Afzalani; Elymaizar, Zulfa; Sulaksana, Indra; Farizal, Farizal (Jurnal Sain Peternakan Indonesia, 2024)
This study aims to determine the profile of short-chain fatty acids (SCFA) and medium-chain fatty acids (MCFA) in goat milk-fed pineapple peel silage.  The pineapple waste was milled and mixed with 5% (w/w) of rice brand, put into an anaerobic plastic bag, and stored for 21 days to produce pineapple peel silage.  The materials used in this research were 12 female Etawa cross-breed dairy goats allocated into randomized block designs with four kinds of feed treatments and three groups of lactation periods.  The feed treatments were P0 (60% forage + 40% concentrate); P1 (30% forage + 30% pineapple peel silage + 40% concentrate); P2 (15% forage + 45% pineapple peel silage + 40% concentrate); P3 (60% pineapple peel silage + 40% concentrate). Forage contains native grass and rubber leaves.  The concentrate consists of 58% bran, 25% fine corn, 6% soybean meal, 9% coconut meal, 1% mineral mixture, and 1% salt.  The variables observed were feed consumption, fat milk, and short-chain and medium-chain milk fatty acids.  The data obtained were analyzed using ANOVA, and if there were differences between treatments, a Duncan test.  The result of this study showed that the use of pineapple peel silage as a forage source had affected the feed consumption (P<0.05) but did not significantly affect SCFA acid and MCFA profile (P> 0.05) in goat milk.  Using pineapple peel silage as forage replacement up to 45 % in Fed, the dairy Ettawa cross-breed (EC) goat’s diet significantly affects the short-chain and medium-chain fatty acids profile.  The content of short-chain fatty acids and medium-chain fatty acids in goat's milk decreases, and there is no musty smell due to the addition of pineapple peel silage in the feed.